An overview of carbapenem-resistant organisms from food-producing animals, seafood, aquaculture, companion animals, and wildlife - Ramírez-Castillo, Flor Y.; Guerrero-Barrera, Alma L.; Avelar-González, Francisco J. (Frontiers in Veterinary Science, 2023)
Carbapenem resistance (CR) is a major global health concern. CR is a growing challenge in clinical settings due to its rapid dissemination and low treatment options. The characterization of its molecular mechanisms and epidemiology are highly studied. Nevertheless, little is known about the spread of CR in food-producing animals, seafood, aquaculture, wildlife, their environment, or the health risks associated with CR in humans. In this review, we discuss the detection of carbapenem-resistant organisms and their mechanisms of action in pigs, cattle, poultry, seafood products, companion animals, and wildlife. We also pointed out the One Health approach as a strategy to attempt the emergency and dispersion of carbapenem-resistance in this sector and to determine the role of carbapenem-producing bacteria in animals among human public health risk. A higher occurrence of carbapenem enzymes in poultry and swine has been previously reported. Studies related to poultry have highlighted P. mirabilis, E. coli, and K. pneumoniae as NDM-5- and NDM-1-producing bacteria, which lead to carbapenem resistance. OXA-181, IMP-27, and VIM-1 have also been detected in pigs. Carbapenem resistance is rare in cattle. However, OXA- and NDM-producing bacteria, mainly E. coli and A. baumannii, are cattle's leading causes of carbapenem resistance. A high prevalence of carbapenem enzymes has been reported in wildlife and companion animals, suggesting their role in the cross-species transmission of carbapenem-resistant genes. Antibiotic-resistant organisms in aquatic environments should be considered because they may act as reservoirs for carbapenem-resistant genes. It is urgent to implement the One Health approach worldwide to make an effort to contain the dissemination of carbapenem resistance.